Nosocomial Outbreak of Coronavirus Disease 2019 by Possible Airborne Transmission Leading to a Superspreading Event. (14th April 2021) - Cheng, Vincent Chi-Chung; Fung, Kitty Sau-Chun; Siu, Gilman Kit-Hang; Wong, Shuk-Ching; Cheng, Lily Shui-Kuen; Wong, Man-Sing; Lee, Lam-Kwong; Chan, Wan-Mui; Chau, Ka-Yee; Leung, Jake Siu-Lun; Chu, Allen Wing-Ho; Chan, Wai-Shan; et al.
Abstract: Background: Nosocomial outbreaks with superspreading of coronavirus disease 2019 due to a possible airborne transmission have not been reported. Methods: Epidemiological analysis, environmental samplings, and whole-genome sequencing (WGS) were performed for a hospital outbreak. Results: A superspreading event that involved 12 patients and 9 healthcare workers (HCWs) occurred within 9 days in 3 of 6 cubicles at an old-fashioned general ward with no air exhaust built within the cubicles. The environmental contamination by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA was significantly higher in air grilles (>2 m from patients' heads and not within reach) than on high-touch clinical surfaces (36.4%, 8 of 22 vs 3.4%, 1 of 29, P = .003). Six (66.7%) of 9 contaminated air exhaust grilles were located outside patient cubicles. The clinical attack rate of patients was significantly higher than of HCWs (15.4%, 12 of 78 exposed patients vs 4.6%, 9 of 195 exposed HCWs, P = .005). Moreover, the clinical attack rate of ward-based HCWs was significantly higher than of nonward-based HCWs (8.1%, 7 of 68 vs 1.8%, 2 of 109, P = .045). The episodes (mean ± standard deviation) of patient-care duty assignment in the cubicles was significantly higher among infected ward-based HCWs than among noninfected ward-based HCWs (6.0 ± 2.4 vs 3.0 ± 2.9, P = .012) during the outbreak period. The outbreak strains belong to SARS-CoV-2 lineage B.1.36.27 (GISAID clade GH) with the unique S -T470N mutation on WGS. Conclusions: This nosocomial point source superspreading event due to possible airborne transmission demonstrates the need for stringent SARS-CoV-2 screening at admission to healthcare facilities and better architectural design of ventilation systems to prevent such outbreaks. Portable high-efficiency particulate filters were installed in each cubicle to improve ventilation before resumption of clinical service. Abstract : A superspreading event due to possible airborne transmission demonstrated the need for stringent severe acute respiratory syndrome coronavirus 2 screening at admission to healthcare facilities and better architectural design of ventilation systems to prevent such outbreaks.